Brazilian population ageing: Differences in well-being by rural and urban areas - Ana Amélia Camarano de Mello Moreira (Institute for Applied Economic Research (ipea), 2015)
The main purpose of this paper is to discuss the relationship between ageing and dependence and the role of social policies in Brazil according to rural and urban areas. In other words, is being elderly in rural areas different from being elderly in urban areas? And if it is found to be so, which dimension of life is affected? How is the social security policy affecting these conditions? As Brazilian national data mask regional differences, the paper also places attention on certain differences between the Northeast (the Brazilian poorest region) and the Southeast (the richest region in this process. In this paper, old age is considered to start at the age of 60. Four dimensions of elderly life are considered, to note: familial arrangements, health conditions, economic activities and income. This is considered taking into account the composition of this group by age and gender according to rural and urban areas. The main data analysed are those from the General Household Surveys (PNAD) of 1981 and 1999. Empirical evidence has shown that in Brazil the relationship between ageing and dependence is not so straightforward. It has shown that the Brazilian elderly are living longer and better. Based on these, one can say that their gains were substantial throughout the studied time period. Poverty and the proportion of elderly without any earnings whatsoever decreased dramatically. They were more marked for the elderly living in rural areas, especially among females. Nevertheless, there is less poverty among the elderly living in urban areas as well. Actually, there is less poverty in general among urban families. Relative better life conditions experienced by the elderly population are contrasted with the effects of the continuous economic crisis experienced by the Brazilian economy. This has affected the young population more through unemployment, violence, drugs, teen-age pregnancy, marital disruption, etc. Poverty increased among the non-elderly urban population aged 25 to 59. As a result, there has been an increase in the time adult children spend as dependents of their parents. The composition of the families with elderly living in has changed to become more complex than the expected 'empty nest'. Summarizing, one can say that there has been a change of status for the elderly within their own families, modifying their traditional role of dependent to that of provider. Three factors have been important in enabling such a situation: the widespread coverage of social security, health policies and improvements in medical technology. Nevertheless, better life condition for the elderly has meant marked costs in terms of social security benefits and health policies. Concern with social security costs is a frequent theme in literature. Nevertheless, the unexpected effects of the spread of social security benefit coverage on the elderly and their families should not be neglected in any public policy evaluation. There are 13 million benefited families. This huge value characterises the social security policy as a modern social policy capable of reducing at lest partially, Brazilian poverty.
Keywords: 330